Studies on in vitro antioxidant activities of nine diff erent fruit tree leaves collected from Mediterranean region of Turkey - Abdurrahman Aktumsek, Sengul Uysal, Gokhan Zengin (Journal of Medicinal Herbs and Ethnomedicine, 2015)
To investigate antioxidant of the methanolic and water extracts obtained from nine different fruit tree leaves (avocado, walnut, mulberry, fig, carob, lemon, pomegranate, grape, and loquat) collected from Mediterranean region of Turkey. The antioxidant activities were evaluated with different in vitro antioxidant assays including phosphomolybdate assay, free radical scavenging assays (â€¢OH, NO, and O2 âˆ’), Î²-carotene/linoleic acid test system, and ferric reducing power. The contents of saponin and tannin in extracts were also determined. The present study suggests that the extracts were good radical scavengers. These results suggest that the extracts examined should be beneficial as a source of natural agents for the food industry and pharmacological applications.